Mass extinction on the Permian - Triassic boundary : geological evidence from the Karoo Supergroup - Snyman, Johanna Elizabeth Wilhelmina (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 1995.